2006
DOI: 10.1182/blood-2006-04-014902
|View full text |Cite
|
Sign up to set email alerts
|

A "liaison dangereuse" between AUF1/hnRNPD and the oncogenic tyrosine kinase NPM-ALK

Abstract: IntroductionAnaplastic large cell lymphoma (ALCL) is a T/null-cell neoplasm characterized by the expression of a hybrid protein comprising an N-terminal partner protein fused to the cytoplasmic portion of the anaplastic lymphoma kinase (ALK) tyrosine kinase. The fulllength ALK protein belongs to the family of receptor tyrosine kinases and is highly conserved across species. 1 In approximately 80% of ALK-positive lymphomas, the hybrid kinase is the NPM-ALK fusion protein that is encoded by the nucleophosmin (NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 62 publications
8
57
0
2
Order By: Relevance
“…With this goal in mind, several large or medium scale proteomic and transcriptomic studies were undertaken by several groups Lim and Elenitoba-Johnson, 2006). New partners have been found that account for different functions of NPM-ALK, such as the regulation of mRNA turnover (Fawal et al, 2006). Among others, proteins regulating cell shape and cytoskeleton plasticity, two important features altered in transformed cells, were identified, leading to investigations of molecules classified as 'cytoskeleton and motility regulators' in the context of ALCLs (Crockett et al, 2004;Cussac et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…With this goal in mind, several large or medium scale proteomic and transcriptomic studies were undertaken by several groups Lim and Elenitoba-Johnson, 2006). New partners have been found that account for different functions of NPM-ALK, such as the regulation of mRNA turnover (Fawal et al, 2006). Among others, proteins regulating cell shape and cytoskeleton plasticity, two important features altered in transformed cells, were identified, leading to investigations of molecules classified as 'cytoskeleton and motility regulators' in the context of ALCLs (Crockett et al, 2004;Cussac et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…COST and NIH-3T3 cells were fixed, permeabilized, and stained as described in the work of Fawal and colleagues (18). Polyclonal anti-HuR and monoclonal anti-ALK1 antibodies were used.…”
Section: Immunofluorescencementioning
confidence: 99%
“…The localisation of AUF1 can be influenced by a variety of factors including: the presence or absence of exons containing nuclear localisation signals [33,34]; interaction with transporters [35] or chaperones [36,37]; protein ubiquitination [13]; and phosphorylation of specific residues [7,38]. At steady-state, most AUF1 isoforms accumulate in the nucleus but are partially relocalised upon exposure of insulin-secreting cells to proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%